Feasibility of quantitative sensory testing in juvenile idiopathic arthritis - Maarten O. Mensink; Niels Eijkelkamp; Dieuwke S. Veldhuijzen; Nico M. Wulffraat (BMC, 2022)
Abstract Objective Juvenile Idiopathic Arthritis (JIA) is a childhood-rheumatic disease with pain as a major early complaint, and in 10-17% pain remains a major symptom. Very few data exist on sensory threshold changes at the knee in JIA, a location in which inflammation often manifests. We determined whether JIA is associated with sensory threshold changes at the knee by using Quantitative Sensory Testing (QST) and established reference values at the knee of children. Methods Sixteen patients with JIA aged 9-18 years with one affected knee and a patient-reported pain by Visual Analog Scale (VAS) > 10 on a 0-100 scale, and 16 healthy controls completed the study and were included for the analysis. QST was assessed in compliance with the German Research Network on Neuropathic Pain (DFNS) standard. Disease severity was determined using Juvenile Disease Activity Score (JADAS. Perceived pain was assessed with a visual analogue scale(0-100). Feasibility of QST was tested in patients aged 6-9. Results Under the age of 9, QST testing showed not to be feasible in 3 out of 5 JIA patients. Patients with JIA aged 9 and older reported an average VAS pain score of 54.3. QST identified a significant reduction in pressure pain threshold (PPT) and increase in cold detection threshold (CDT) compared to healthy controls. PPT is reduced in both the affected and the unaffected knee, CDT is reduced in the unaffected knee, not the affected knee. Conclusion In a Dutch cohort of Patients with JIA, QST is only feasible from 9 years and up. Also, sensory threshold changes at the knee are restricted to pressure pain and cold detection thresholds in Patients with JIA. Perspective This article shows that in a Dutch population, the extensive QST protocol is only feasible in the age group from 9 years and older, and a reduced set of QST tests containing at least pressure pain thresholds and cold detection thresholds could prove to be better suited to the pediatric setting with arthritis.